THE EFFECT OF RAPID URBANIZATION ON THE PHYSICAL MODIFICATION OF URBAN AREA - FULADLU, Kamyar; RİZA, Müge; İLKAN, Mustafa (RENECON International, 2018)
Today rapid urbanization is a major challenge for many cities. In 2007 urban population started to exceed the rural population. Increasingly, scholars and governments discuss the effects of this trend on future development of cities. It is obvious that any kind of urban development should be controlled and regulated, otherwise the outcome could lead to a chaotic and unsustainable development. Besides, it may result in environmental problems like air pollution, heat islands, urban climate and etc. Unfortunately, this kind of physical modification practically have not been considered by the planners and designers. The current study is grounded on recent literature review and tries to concentrate on this problem mainly from the development and construction performance perspective. Moreover, the current study attempts to classify the effective variables under the urban form, urban geometry, and urban population.
Keywords: Urban Form; Urban Material; Urban Population; Sustainability; City Planning